Nitrogen doses in the growth of Calceolaria x herbeohybrida in pot - Winhelmann, Mara Cíntia; Grzeça, Gislaine Taís; Paris, Priscila; Tedesco, Marília; Palolazzi, Joana; Avrella, Eduarda Demari; Fior, Claudimar Sidnei; Schafer, Gilmar (Ornamental Horticulture, 2017)
Calceolaria x herbeohybrida Voss (pocketbook plant, calceolaria) is an herbaceous perennial and floriferous species that can be grown in pots or beds. Nitrogen is usually the most required nutrient, being necessary to conduct studies in order to provide useful information for agronomic practices. Thus, this study aimed to evaluate nitrogen doses in the growth of Calceolaria x herbeohybrida in pots. Initially, assorted and pelleted calceolaria seeds were sow in multicellular trays containing a commercial substrate based on peat and kept in a floating irrigation system in a protected environment. At the greenhouse, seedlings with four true leaves were transplanted into 1 L pots containing the same substrate and a drip irrigation system. The treatments consisted of different nitrogen doses (0.0, 0.5, 1.0, 2.0 or 4.0 g of N L-1) applied weekly using ammonium nitrate as source. Fertilization with P and K was also done, and all treatments received de same dose. At the end of the experimental period, shoot length, leaf area, shoot and root dry matter, number of buds and flowers, chlorophyll a, b and total chlorophyll were evaluated. The experimental design was completely randomized with four replications and five plants per plot. The data were treated with ANOVA and the means were treated with regression analysis using the SigmaPlot 11.0 software. There was no survival of plants at the highest N dose (4.0 g L-1). Shoot length showed a quadratic behavior, with a maximum point at 1.25 g L-1, where plants reached 13.3 cm. There was a similar behavior for the variable leaf area, with the highest point at 1.24 g L-1. Shoot dry mass presented the maximum point at a dose of 1.20 g L-1, resulting in 4.21 g of dry matter. Regarding root dry matter, no equation could be adjusted. For the variable number of buds and flowers, the highest point was at a dose of 1.20 g L-1, with 35.86 buds and flowers per plant. For chlorophyll a, b and total chlorophyll, the maximum point was at 1.5 g L-1. The ideal nitrogen dose is between 1.2 and 1.5 g L-1 for most variables.